2015
DOI: 10.7883/yoken.jjid.2014.165
|View full text |Cite|
|
Sign up to set email alerts
|

Genotype Diversity and Quasispecies Development of <i>Helicobacter pylori</i> in a Single Host

Abstract: SUMMARY:Infection with different strains of Helocobacter pylori and emergence of new genomic variants during their long-term gastric colonization are assumed to be the main reasons for eradication failure. We used genotyping and arbitrarily primed PCR fingerprinting (RAPD) to detect relatedness and genetic variations among H. pylori single isolates from each patient in Iran. Multiplex-PCR amplification of gene alleles encoding the virulence factors vacA (m/s), cagA, and iceA (A1/A2) and comparison of RAPD patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Apart from medical cost problem of the TR regimen, given issues on increased prevalence of drug resistance of H. pylori worldwide, tailored approaches in treating H. pylori infection should be considered further. The possible reasons for treatment failure in the TR group are as follows[28,29]. First, although H. pylori has traditionally been regarded as a homogenous organism, there is increasing evidence that populations of H. pylori in humans show wide diversity[29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from medical cost problem of the TR regimen, given issues on increased prevalence of drug resistance of H. pylori worldwide, tailored approaches in treating H. pylori infection should be considered further. The possible reasons for treatment failure in the TR group are as follows[28,29]. First, although H. pylori has traditionally been regarded as a homogenous organism, there is increasing evidence that populations of H. pylori in humans show wide diversity[29].…”
Section: Discussionmentioning
confidence: 99%
“…First, although H. pylori has traditionally been regarded as a homogenous organism, there is increasing evidence that populations of H. pylori in humans show wide diversity[29]. The quasi-species development of H. pylori in a single host might result in treatment failure even after a tailored eradication strategy based on the presence of a 23S ribosomal RNA point mutation[28]. Second, a DPO-PCR-based evaluation is limited to detecting mutations of A2142G and A2143G in 23S rRNA, and other mutations, such as the A2144G or A2142C mutation of H. pylori , cannot be detected[20,30].…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, it was estimated that 80% of the adult population have a history of infection with these bacteria (4). However, recent studies revealed that this rate has decreased up to 40% in some cities with higher socioeconomic status (5).…”
Section: Introductionmentioning
confidence: 98%
“…The large genetic variation observed among clinical strains of H. pylori is thought to be an important determinant in the specific local establishment of this colonization and determines in large part the development of the potential disorders that result from the infection [ 6 ]. The remarkable genetic and phenotypic diversity observed in H. pylori is thought to be driven by the need to adapt to the harsh and patient specific conditions of the gastric environment that often result in the genesis of various subpopulations (quasispecies) within single patients [ 7 ]. This results in each infected person potentially carrying genetically unique microorganisms existing only in that particular patient [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable genetic and phenotypic diversity observed in H. pylori is thought to be driven by the need to adapt to the harsh and patient specific conditions of the gastric environment that often result in the genesis of various subpopulations (quasispecies) within single patients [ 7 ]. This results in each infected person potentially carrying genetically unique microorganisms existing only in that particular patient [ 7 , 8 ]. Depending on the presence of specific H. pylori virulence factors such as dupA , cagA , vacA and homB the bacterium usually colonizes the antral mucosa of human stomach [ 8 ].…”
Section: Introductionmentioning
confidence: 99%